2004
DOI: 10.1097/00061198-200402000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Corneal Drying on Central Corneal Thickness

Abstract: Corneal thickness may significantly decrease during 1 minute of drying. Decreased thickness may result in underestimation of applanated pressure as well as central corneal thickness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 16 publications
0
25
0
1
Order By: Relevance
“…Previous studies showed a decrease in CCT in dry-eye syndrome, because of the osmolality of tear film and hypertonic tear film. 8,9 According to our results, a decrease in CCT is not related with corneal biomechanical changes in dry eye. In another study, an increase in CCT values was seen at night but corneal viscoelasticity did not change.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Previous studies showed a decrease in CCT in dry-eye syndrome, because of the osmolality of tear film and hypertonic tear film. 8,9 According to our results, a decrease in CCT is not related with corneal biomechanical changes in dry eye. In another study, an increase in CCT values was seen at night but corneal viscoelasticity did not change.…”
Section: Discussionmentioning
confidence: 55%
“…7 Another factor is central corneal thickness (CCT), which is shown to be decreased in dry eye. 8,9 The consensus is that IOP measurement using GAT may be falsely reduced in patients with thin corneas. 7 All these corneal changes seen in dry eye can affect the corneal viscoelasticity, which can be measured with the Ocular Response Analyser (ORA; Reichert Ophthalmic Instruments, Buffalo, NY, USA).…”
Section: Introductionmentioning
confidence: 99%
“…Third, all IOP measurements using the three tonometers were taken after instillation of anesthetic drops, which may change the corneal biomechanical parameters. 17 However, in the IOPen learning curve, we found that without corneal anesthesia, the IOPen was uncomfortable for most subjects. Also the drops were instilled before the IOP measurements and the influence for the corneal properties modifications is similar for all tonometers.…”
Section: Gendermentioning
confidence: 84%
“…9,10,11,13 In our study dry eye tests were not taken into consideration when comparing groups so we do not know how many patients have dry eye which may affect CCT as some studies show lower CCT in dry eye patients. 25,26 One of the limitations of this study is that the systemic therapy of patients are unknown. We do not know medications that patients currently use or used in the past that may have an effect on ORA parameters directly or indirectly by influencing IOP and CCT.…”
Section: Discussionmentioning
confidence: 97%